Atypical Eruptive Xanthoma: A Condition Confused With Monkeypox Rash - Thewjitcharoen, Yotsapon; Saiwaew, Natthakan; Nakasatien, Soontaree; Himathongkam, Thep (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Since May 2022, monkeypox outbreaks have been reported in several countries outside Africa. The typical skin lesions of monkeypox begin as papules that appear in possible areas of inoculation, such as the skin or mucous membranes, followed by generalized pustules. Systemic symptoms appear simultaneously or a few days earlier than the lesions.